SURAT PERNYATAAN KERELAAN DARI JANDA DALAM PERISTIWA TURUN WARIS TERHADAP HARTA BAWAAN PEWARIS - Arofah Afridha Zaelani; Nugraheni, Destri (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2024)
Based on the research results, it can be concluded that (1) the Sleman and Bantul Regency Land Offices use customary law as the basis for making regulations regarding the inheritance process because they are based on custom. The Sleman and Bantul Regency Land Offices require a statement of willingness from the widow not to receive her share of inheritance in the inheritance process. The absence of this letter of willingness can cause the inheritance process to not be carried out. (2) The position of the widow's statement of willingness not to receive a share of the inheritance in terms of Islamic inheritance law is contrary to the legal basis of the ijbari principle and the individual principle. However, if the widow agrees not to receive a share of the heir's inheritance then this refers to a peace or elimination of disputes which can be called Ishlah.